Sexual Behaviors of U.S. Men by Self-Identified Sexual Orientation: Results From the 2012 National Survey of Sexual Health and Behavior. Issue 4 (1st April 2016) - Dodge, Brian; Herbenick, Debby; Fu, Tsung-Chieh (Jane); Schick, Vanessa; Reece, Michael; Sanders, Stephanie; Fortenberry, J. Dennis
ABSTRACT: Introduction: Although a large body of previous research has examined sexual behavior and its relation to risk in men of diverse sexual identities, most studies have relied on convenience sampling. As such, the vast majority of research on the sexual behaviors of gay and bisexual men, in particular, might not be generalizable to the general population of these men in the United States. This is of particular concern because many studies are based on samples of men recruited from relatively "high-risk" venues and environments. Aims: To provide nationally representative baseline rates for sexual behavior in heterosexual, gay, and bisexual men in the United States and compare findings on sexual behaviors, relationships, and other variables across subgroups. Methods: Data were obtained from the 2012 National Survey of Sexual Health and Behavior, which involved the administration of an online questionnaire to a nationally representative probability sample of women and men at least 18 years old in the United States, with oversampling of self-identified gay and bisexual men and women. Results from the male participants are included in this article. Main Outcome Measures: Measurements include demographic characteristics, particularly sexual identity, and their relations to diverse sexual behaviors, including masturbation, mutual masturbation, oral sex, vaginal sex, and anal sex. Behaviors with male and female partners were examined. Results: Men of all self-identified sexual identities reported engaging in a range of sexual behaviors (solo and partnered). As in previous studies, sexual identity was not always congruent for gender of lifetime and recent sexual partners. Conclusion: Patterns of sexual behaviors and relationships vary among heterosexual, gay, and bisexual men. Several demographic characteristics, including age, were related to men's sexual behaviors. The results from this probability study highlight the diversity in men's sexual behaviors across sexual identities, and these data allow generalizability to the broader population of gay and bisexual men, in particular, in the United States, which is a major advancement in research focused on individuals in a sexual minority.